Perceived Problems and Suggestions of Farmers regarding Kisan Call Centre - Goyal, Shashikant; Jirli, Basavprabhu; G., Manunayaka (Indian Journal of Extension Education, 2019)
Availability of appropriate information at right time and communication of information have been most important factors for increasing agricultural production. There is flood of information but which information will be useful where and for whom and how to take it to the needy people has been a big challenge. Farmers need a bunch of information in agriculture at every stage ranging from improved crop cultivation practices, weather forecast, hybrid seeds, inputs for cultivation, insect, pest and disease management, storage facility and price of agricultural produce. Farmers can get information from number of ways including trial and error. Important information related to agriculture is neither symmetric nor costless. The study was conducted in Varanasi district of Utter Pradesh to know the problems faced by the farmers to using kisan call centre. Ex-post facto design was used for the research and snow ball sampling was used for selecting150 respondents and data was collected with the help of well-prepared schedule. Data was analyzed by using chi squire test for finding association among dependent and independent variables.
Keywords: Communication gap; Information; Technology